FORMATION OF THE DISCIPLINARY CHARACTER OF LEARNERS GOTHROUGH REWARD METHODS AND PUNISHMENT IN SOCIAL STUDIES SUBJECTS AT SMPN 2 ARJASA - Muhammad Aldin Hamdani; Abdul Karim; Lilik Wahyuni (SOLIDARITY: Journal of Social Studies, 2022)
ABSTRACK The educational process always produces a goal such as learning achievement and not all students can get good learning achievement because there are still many students who do not dare to be active in a learning activity because the character of self-discipline is still lacking. Therefore it is necessary to have a stimulus from a teacher or stimulation from the teacher so that students can be more active in the learning process and also students can be more disciplined in making a decision whether learning is successful or not depending on how the teacher carries out good learning activities. This study uses descriptive qualitative data collection using interviews. The type of research using field research (Field Research) with analysis of data reduction, display and verification. The use of rewards is proven to increase student discipline because students tend to repeat positive actions to get rewards. Likewise, the punishmant is very effective in training student discipline so that it does not repeat itself. This requires the creativity of a teacher to create a pleasant learning atmosphere, including the use of reward which is one of the drivers, encouragement and motivation for students in increasing student discipline. Keyword : Character; Reward And Punishmant; Learners